Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/md.0000000000015789
|View full text |Cite
|
Sign up to set email alerts
|

Development of model to predict end-stage renal disease after coronary artery bypass grafting

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, type of surgery was not a significant predictor in our study, which may be due to the small number of aortic surgery included in our data. Old age and baseline renal function were also significant in our study [2,17]. In addition, body mass index and history of diabetes mellitus were also significant in our study; both are known risk factors of CKD in the general population [25,26].…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…However, type of surgery was not a significant predictor in our study, which may be due to the small number of aortic surgery included in our data. Old age and baseline renal function were also significant in our study [2,17]. In addition, body mass index and history of diabetes mellitus were also significant in our study; both are known risk factors of CKD in the general population [25,26].…”
Section: Discussionsupporting
confidence: 61%
“…To our knowledge, only a few previous studies investigated the risk factors of new-onset CKD after cardiac or thoracic aortic surgery [ 2 , 17 , 37 ]. A previous retrospective cohort study also reported that AKI is a significant predictor of CKD after cardiac surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations